Development of Comic Strip as Learning Media to Teach English Writing Skills in Vocational High School - Zahrok, Rica Fatimatuz; Rofi'ah, Siti; Makrifah, Istina Atul Makrifah Atul (Universitas Pahlawan Tuanku Tambusai, 2026)
This study developed a comic strip learning media using the Research and Development (RD) type. The subjects of this study were one English teacher at SMK Islam 1 Bitar, validator, and class X TKJ students. The types of data used in this study were qualitative data from classroom observation and interviews with teacher and quantitative from questionnaires given to validators and students. The results of the instrument validation obtained 85,71%. The results of the material validation obtained a value of 95% and media validation obtained 97,5%. It can be concluded that the results of the comic strip media validation obtained the criteria of